Happy Triangles

Geometry Level 4

Call a triangle "happy" if it has consecutive integer side lengths and integral area. The first two "happy" triangles are the 3-4-5 and 13-14-15 triangles. What is the perimeter of the third "happy" triangle?


The answer is 156.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Garrett Clarke
Jun 17, 2015

The best solution to this problem is to refer to an equation known as Heron's Formula. This is an equation for the area of a triangle that requires only the lengths of its sides. It is as follows:

For a triangle with sides a a , b b , & c c :

A = s ( s a ) ( s b ) ( s c ) \large A = \sqrt{s(s-a)(s-b)(s-c)} where s = a + b + c 2 s = \Large\frac{a+b+c}{2}

Our question asks for triangles with consecutive side lengths. We'll let a = x 1 a = x-1 , b = x b = x , and c = x + 1 c = x+1 . This means that our solution will be of the form 3 x 3x . First we'll plug in out numbers into our formula for s s .

s = x 1 + x + x + 1 2 = 3 2 x s = \Large\frac{x-1+x+x+1}{2} = \frac{3}{2} x

Now we'll plug in our values of s s , a a , b b , & c c into our formula for the area.

A = 3 2 x ( 3 2 x x + 1 ) ( 3 2 x x ) ( 3 2 x x 1 ) \large A = \sqrt{\frac{3}{2} x(\frac{3}{2} x-x+1)( \frac{3}{2} x-x)( \frac{3}{2} x-x-1)}

A = 3 2 x ( 1 2 x + 1 ) ( 1 2 x ) ( 1 2 x 1 ) \large A = \sqrt{\frac{3}{2} x(\frac{1}{2} x+1)( \frac{1}{2} x)( \frac{1}{2} x-1)}

A = x 2 3 ( 1 2 x + 1 ) ( 1 2 x 1 ) \large A = \frac{x}{2} \sqrt{3(\frac{1}{2} x+1)( \frac{1}{2} x-1)}

A = x 2 3 ( 1 4 x 2 1 ) \large A = \frac{x}{2} \sqrt{3(\frac{1}{4} x^2-1)}

A = x 4 3 ( x 2 4 ) \large A = \frac{x}{4} \sqrt{3(x^2-4)}

For A A to be an integer, we need two things to happen:

1 1 . 3 ( x 2 4 ) 3(x^2-4) has to be a square number

2 2 . We need to check if 4 x 3 ( x 2 4 ) 4\mid x\sqrt{3(x^2-4)}

Let's begin by finding numbers that satisfy 3 ( x 2 4 ) = n 2 3(x^2-4) = n^2

Observe that x x cannot be divisible by 3 because we need 3 x 2 4 3\mid x^2-4 to be true.

( 3 n ) 2 0 (3n)^2 \equiv 0 (mod 3 3 ) ( 3 n ) 2 4 2 \Longrightarrow (3n)^2-4 \equiv 2 (mod 3 3 )

Also not that x x cannot be odd. If x x was odd, the 3 ( x 2 4 ) 3(x^2-4) would have to be an odd square, and x 3 ( x 2 4 ) x\sqrt{3(x^2-4)} would be odd as well, meaning that 4 x 3 ( x 2 4 ) 4\nmid x\sqrt{3(x^2-4)}

This leaves us to check only numbers of the form 6n-2 and 6n+2. This narrows down our search a bit.

3 ( ( 6 n 2 ) 2 4 ) = 3 ( 36 n 2 24 n + 4 4 ) = 6 2 ( 3 n 2 2 n ) 3((6n-2)^2-4)=3(36n^2-24n+4-4)=6^2(3n^2-2n)

3 ( ( 6 n + 2 ) 2 4 ) = 3 ( 36 n 2 + 24 n + 4 4 ) = 6 2 ( 3 n 2 + 2 n ) 3((6n+2)^2-4)=3(36n^2+24n+4-4)=6^2(3n^2+2n)

So either 3 n 2 2 n 3n^2-2n or 3 n 2 + 2 n 3n^2+2n must be a perfect square.

From here it's pretty simple to check values of n n to see what works and what doesn't. Letting n = 1 n=1 in our 1st equation yields x = 4 x=4 as a solution, and letting n = 2 ) n=2) yields x = 14 x=14 , and our next solution doesn't come until n = 9 n=9 where 3 × 9 2 2 × 9 = 225 = 1 5 2 3\times9^2-2\times9 = 225 = 15^2

x = 6 ( 9 ) 2 = 52 3 x = 156 x=6(9)-2=52 \Longrightarrow 3x = \boxed{156}

Note that from 3 ( x 2 4 ) \sqrt{3(x^2-4)} , we want to find a number x x such that x 2 4 = 3 y 2 x^2-4=3y^2 , which dissolves into a Pell's Equation, which we can solve to get x = 52 x=52 as the next solution.

Sharky Kesa - 4 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...